Nomenclalure des composés chimiques - Kaczmarek, Karolina (Studia Romanica Posnaniensia, 2009)
This article presents the mechanisms of the inorganic chemistry nomenclature formation in French language. It shows the structure and the way of presenting the names of chemical compounds either descriptively or by giving the structural formulas’ characteristics, their transcription and order of reading the letters. The text specifies the rules of naming a chemical compound, according to the criteria of IUPAC (Union of Pure and Applied Chemistry), the organisation responsible for digesting the chemical nomenclature. The article contains the transcription chart and the manner of reading the structural formula, also called latero-numerical. Additionally, there is information conceming the usage of the common names given, still remaining in use next to the names compatible with those of IUPAC. Particular types of chemical compounds have served as models for description of other nomenclature formation rules from the simplest structures to the complicated compound ones. A short summary presents the relations and similarities between the names of particular types of chemical compounds.